PENGEMBANGAN PERANGKAT BERORIENTASI MODEL PEMBELAJARAN LANGSUNG PADA POKOK BAHASAN SISTEM PERNAPASAN MANUSIA DI KELAS V SDN KETINTANG I GAYUNGAN SURABAYA - Nancy katili (Jurnal Inovasi, 2009)
This research is developing research, because in this research is developed learning materials of mathematical and natural sciences (IPA) for elementary education oriented to direct-learning model. Dick and Carey's development of learning materials are used in this research. Learning materials developed covers learning plan (RPP), student activity sheet (LKS), student teaching materials and the test of the result of student learning (THB). Those are tried out to the fifth class students of SDN Ketintang I Gayungan Surabaya. These indicate that during direct-learning activity, student involved actively. The feasibility of learning during direct-learning activity from the three learning plans (RPP 01 - RPP 03) is categorized very good. Student response to the learning consists of enthusiasm and motivation. Student enthusiasm to the learning indicates that student attention is good, they can correlate the lesson with their everyday life, they have high believe in learning activity, and they satisfy following this direct-learning. Student motivation indicates that they are motivated during teaching learning process using direct-learning model. It can be seen from the score obtained in motivation questionnaires is high. The result of student learning at try-out I and II indicates that the feasibility of student in classical is above complete means specified, i.e. 0.86